Antibiotic use among children under five years with diarrhea in rural communities of Gulu, northern Uganda: a cross-sectional study - Lanyero, Hindum; Ocan, Moses; Obua, Celestino; Stålsby Lundborg, Cecilia; Nanzigu, Sarah; Katureebe, Agaba; Kalyango, Joan N.; Eriksen, Jaran (BMC Public Health, 2021)
Diarrhea is the second leading cause of mortality in children under 5 years of age globally, and the risk of death increases with practices such as restriction of fluid intake and inappropriate use of antibiotics. We determined the prevalence of antibiotic use in managing diarrhea in children under 5 years of age in rural communities of Gulu district, northern Uganda. Method: A cross-sectional study among children under 5 years with diarrhea, from households selected using multistage sampling. A researcher administered questionnaire was used to obtain data from caregivers of these children. Results: Of the 856 children recruited, 318 (37.1%, 318/856) had experienced diarrhea, where 263 (82.7%, 263/318) had diarrhea with acute respiratory infections (ARIs), and 55 (17.3%, 55/318) had diarrhea without ARIs. The majority (89.6%, 285/318) of the children had non-bloody diarrhea. A high proportion (82.8%) of the children with non-bloody diarrhea also had ARIs. Bloody diarrhea was reported for 33 (10.4%) children including those with ARIs, and only 6 of these (18.2%) children had bloody diarrhea without ARIs. Of the 318 children with diarrhea, over half (52%, CI: 46–57) were administered antibiotics. Of the 55 children who had diarrhea without ARIs, over a third (38%, CI: 26–51) were administered antibiotics. Similarly, of the 263 children with diarrhea and ARIs, 54% (CI: 48–60) were treated with antibiotics. The determinants of antibiotic use included; children living in peri-urban settings (AOR: 3.41, CI: 1.65–7.08, P = 0.001), getting treatment from health facility (AOR: 1.76, CI: 1.06–2.93, P = 0.029), and having diarrhea with ARIs (AOR: 3.09, CI: 1.49–6.42, P = 0.003). Conclusion: Antibiotic use is common among children under 5 years with diarrhea in rural communities of northern Uganda.
Keywords: Antibiotic; Children; Diarrhea; Rural communities of Gulu; Northern Uganda